The teaching of literature with university students of Italian as a foreign language: a path through Leonardo Sciascia’s “Sicilianness” - Pioli, Marco (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
With the rise of communicative methods, since the 1970s literature has been gradually relegated to the margins of the teaching of foreign languages and only recently the pedagogical debate has reconsidered its potentialities. Given the previous premise, the present study proposes a reflection on the peculiarities of literary education in foreign language teaching at university, a research field which has been a bit neglected by scholars and specialized publishing houses so far. The references to theory will be followed by the presentation of some teaching strategies experimented in a university course dedicated to Leonardo Sciascia’s Hispanophilia and to its intertwining with the peculiar way in which the Sicilian author expressed his Italianness through the attachment to his native island.